2017
DOI: 10.3390/app7100990
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Two Dimensional Tomography Reconstruction of Temperature and Gas Concentration in a Combustion Field Using TDLAS

Abstract: Based on tunable diode laser absorption spectroscopy (TDLAS), two-dimensional (2D) distribution reconstructions of gas concentration and temperature are realized using an algebraic reconstruction technique (ART). The influence of the beam distribution and grid size on combustion field reconstruction is investigated to attain optimal reconstruction results with a limited number of beams. Under limited optical-path numbers, it shows that a better spatial resolution is attainable only when the laser beam paths ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Accurate and stable gas detection plays an important role in air pollution prevention and industrial production [1][2][3][4]. With the development of laser absorption spectroscopy and optoelectronic devices [5][6][7][8], TDLAS and other related technologies are gradually applied, and have been widely used in industrial production, natural environment, diagnosis and treatment, food and many other industries [9][10][11][12]. In the process of the development of laser absorption spectrum measurement Pol.…”
Section: Followingmentioning
confidence: 99%
“…Accurate and stable gas detection plays an important role in air pollution prevention and industrial production [1][2][3][4]. With the development of laser absorption spectroscopy and optoelectronic devices [5][6][7][8], TDLAS and other related technologies are gradually applied, and have been widely used in industrial production, natural environment, diagnosis and treatment, food and many other industries [9][10][11][12]. In the process of the development of laser absorption spectrum measurement Pol.…”
Section: Followingmentioning
confidence: 99%
“…In the combustion process, temperature and gas component concentration are essential parameters to analyze the combustion state and chemical reaction process. Among them, temperature represents the amount of heat, the energy released in the combustion process the efficiency, and component concentration represents whether the fuel composition and combustion are completed [2]. To improve combustion efficiency and control pollution emissions, it is necessary to measure the proper distribution of temperature concentration and other flow field parameters in the combustion process [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tunable diode laser absorption tomography (TDLAT) is a suitable tool for understanding the combustion process by allowing 2D analysis of temperature and species concentration with non-contact fast-response. Therefore, it has been developed with various TDLAT techniques for measuring 2D temperature and species concentration in combustion fields [10][11][12][13][14]. Deguchi et al demonstrated a 2D temperature distribution measurement by TDLAT on Bunsen-type flame burners and gasoline engines [10].…”
Section: Introductionmentioning
confidence: 99%